2018
DOI: 10.1177/0268355518805686
|View full text |Cite
|
Sign up to set email alerts
|

A novel endovenous scaffold for the treatment of chronic venous obstruction in a porcine model: Histological and ultrastructural assessment

Abstract: Objective To investigate the biological effects of a novel endovenous scaffold in a porcine model. Methods Petalo is a compliant venous scaffold implanted into the internal jugular veins of 12 healthy pigs. The pigs were sacrificed at one, two, three, and six months, respectively. Microscopic investigations were performed at two blinded laboratories. Results Neo-intima formation progressively covering up the stent metallic bars was observed. The inflammatory response of the venous wall showed a peak after thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Dedicated venous stents were not available until very recently. 4,9,27,[33][34][35][36]40 The preclinical study about a new scaffold, denominated Petalo CVS, has been shown that it could have the ideal characteristics of a venous stent, but it is necessary a first in man study to affirm it. 9…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Dedicated venous stents were not available until very recently. 4,9,27,[33][34][35][36]40 The preclinical study about a new scaffold, denominated Petalo CVS, has been shown that it could have the ideal characteristics of a venous stent, but it is necessary a first in man study to affirm it. 9…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if the stent has an anchor point, that permits a passive anchoring, the radial force required to avoid migration will be lower and the risk of myointimal hyperplasia and restenosis will decrease too. 1,2,4,11,22,35,38,40,41 Undersized stent and residual stenoses at the inflow or outflow segments can induce significant complications, such as chronic occlusion or persistence of symptoms. 1,3,42 The ideal venous stent has not instent restenosis.…”
Section: Venous Stent Versus Arterial Stentmentioning
confidence: 99%
See 3 more Smart Citations